THE INFLUENCE OF MIX MARKETING STRATEGIES AND CONSUMER PREFERENCES ON CONSUMER LOYALTY FOR ALGHIFARI RED GINGER DRINK PRODUCTS - Ramli, Irna Marliana; Dasipah, Euis; Permana, Nendah Siti (Journal of Sustainable Agribusiness, 2024)
Performance of the Marketing Mix Strategy (Mix Marketing Strategic) which includes the dimensions: product; prices; place; promotion on the Alghifari red ginger beverage business in Cianjur City obtained an achievement of 78.26% with good criteria. Performance of consumer preferences which includes dimensions / attributes: taste, aroma, colour, properties and packaging for consumers of Alghifari red ginger drink in Cianjur City achieved 79.27% good criteria. Demonstration of Consumer Loyalty which includes dimensions: taste, aroma, colour, properties and packaging of the Alghifari red ginger drink in Cianjur City achieved 79.08% of the Good criterion. There is a positive correlation between the Marketing Mix Strategy and the Consumer Preferences of Alghifari Red Ginger Drink as indicated by the correlation coefficient number r = 0.889 meaning that the better the Marketing Mix strategy is implemented, the better the consumer preference level will be. Marketing Mix Strategy and Consumer Preference have a significant effect on Consumer Loyalty of Alghifari Red Ginger Drink. The contribution of the influence of Consumer Preference is 70.74% greater than the contribution of the Marketing Mix Strategy of 19.50%. The remaining 9.76% is influenced by other factors.